Decentralized trustworthiness score management with smart contracts on the trustlend platform - Wisnu Uriawan; Youakim Badr; Omar Hasan; Lionel Brunie (IET Blockchain, 2024)
Abstract The personal lending marketplace, known as Peer‐to‐Peer (P2P) lending, has increased globally. However, providing unsecured loans to peers without requiring collateral remains a challenge. A platform called TrustLend is proposed to enable trustworthy transactions in the personal lending application. The platform attempts to eliminate or minimize the collateral requirement. The trustworthiness score adds to this platform's variable selection rules and can help lenders decide on reliable candidates as borrowers. The prototype implementing the TrustLend platform based on Ethereum smart contracts that use the trustworthiness score is also described and it is illustrated with a Decentralized Application (DApp) case study and customized smart contracts. The prototype demonstrates fundamental features and supports borrowers, lenders, and recommenders in establishing proposals and approvals. Finally, the prototype shows how end‐users can easily access loans with reduced collateral without hidden costs and swift transactions.